Efeitos das iniciativas de comunicação digital das empresas na repercussão protagonizada pelos consumidores no twitter - Silva, Nicolas Motta da (2012)
The expansion of Internet usage for the masses favors the establishment of a new form of communication between companies and their customers. The present study aimed to increase knowledge about this relationship: the companies communication efforts over the internet and how the public reacts to these initiatives. To this end, we tried to identify factors that generate impact in terms of word of mouth about the companies; observe the citations on a particular brand, its relationship with some communication initiative, and the sentiment contained in these mentions. To complement the research and enrich the knowledge about the subject, we measured the amount of citations made by people on Twitter about a brand, during the period of 6 months. Analyzing the contents of this quote it was revealed that the various communication initiatives - digital or not - have repercussions in terms of online word of mouth. Television advertisements, promotions, contests and other factors that are not direct initiatives of the companies are reason of conversations between people in the internet social networks. Besides being able to observe the manifestation of the people about the initiatives of the companies, it was important to identify the need for companies to be alert to the content of the information about them on social networks. With all the power that consumers, when engaged, have, is essential for companies to relate, answer questions and to retract when appropriate. Although it has made a thorough search on the subject, by no means exhaust the joints on it, is extremely timely to conduct research to address other facets of the relationship between the consumer and the companies through internet social networks